Prevalence of osteoporosis in liver cirrhosis - Ümit Bilge DOĞAN; Seren ÖZENİRLER and Mehmet ARAÇ and Ayhan KARAKOÇ and Ziya ÖZTÜRK and Mehmet CİNDORUK and Uğur KANDİLCİ (Turkish Journal of Gastroenterology, 2019)
-